Effectiveness of Pediatric Palliative Care Education on Pediatric Clinicians. (December 2017) - Peng, Niang-Huei; Lee, Cheng-Han; Lee, Min-Chun; Huang, Li-Chi; Chang, Yue-Cune; DeSwarte-Wallace, Joetta
A lack of knowledge and skills in pediatric palliative care may create hesitation in caring for children with serious life-threatening conditions and their families. Our research examined the effectiveness of pediatric palliative care training for pediatric clinicians. A pretest–posttest study provided educational training in pediatric palliative care to pediatric clinicians and used a pretest and a posttest to assess outcomes. Fifty pediatric clinicians attended this research with 83.3% response rate. After training, participants reported significantly increased confidence in a variety of areas, including providing emotional support to clinicians, personal knowledge, skills, and communication; ethical and legal concerns; and providing emotional support to dying children and their families. Results showed a significant main effect of training on confidence levels ( p < .000). This suggests that education can effectively boost pediatric clinicians' confidence regarding providing pediatric palliative care and therefore should regularly be provided to clinicians.